Fatigue Fracture Analysis of Elevator Reducer Output Shaft - Yang Li; Rui Zhiyuan; Luo Dechun; Cao Hui; Hu Xuchun; Lu Shihui (Jixie chuandong)
In order to find the cause of an elevator reducer output shaft fracture,the chemical property,mechanical property and material property are obtained through the experimental method,the theoretical calculation of stress,fatigue strength and fatigue life are carried out. The fatigue analysis of keyway with different curvature radius carried out by using the finite element method（ FEM）,and comparing with the theoretical result,it is concluded that the reason of fracture is higher notch effect of low curvature radius on the keyway. The results show that high stress on axes keyway corner decrease with the increase of curvature radius,as the fatigue life become longer.